2015
DOI: 10.1007/s12010-014-1472-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Nargenicin A1 and Generation of Novel Glycosylated Derivatives

Abstract: Nargenicin A1, an antibacterial polyketide macrolide produced by Nocardia sp. CS682, was enhanced by increasing the pool of precursors using different sources. Furthermore, by using engineered strain Nocardia sp. ACC18 and supplementation of glucose and glycerol, enhancement was ~7.1 fold in comparison to Nocardia sp. CS682 without supplementation of any precursors. The overproduced compound was validated by mass spectrometry and nuclear magnetic resonance analyses. The novel glycosylated derivatives of purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The analyses of OPME reactions with curcumin revealed that the formation of monoglycosides was favored at higher concentration of substrate, whereas the lower concentration of substrate was favorable for diglycosides. These OPME systems have proven their efficiency by successful glycosylation of α-mangostin [28] and nargenicin A(1) [31].…”
Section: Glycosylation Of Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses of OPME reactions with curcumin revealed that the formation of monoglycosides was favored at higher concentration of substrate, whereas the lower concentration of substrate was favorable for diglycosides. These OPME systems have proven their efficiency by successful glycosylation of α-mangostin [28] and nargenicin A(1) [31].…”
Section: Glycosylation Of Curcuminmentioning
confidence: 99%
“…The one-pot multienzyme (OPME) approaches are often employed for the synthesis of diverse kinds of glycoconjugates. Our group has successfully developed and applied the efficient OPME systems for the synthesis of glycosides of α-mangostin [28], nargenicin A(1) [31], and resvera-A [32]. Such methods are more efficient and cheaper than the chemical methods, which involve several protection/deprotection steps before any product can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, heterologous expression of acetyl-CoA carboxylase complex from S. coelicolor A3 (2) in Nocardia sp. CS682 resulted in a substantial increase in the pool of malonyl-CoA (Maharjan et al 2012), and subsequent feeding led to the enhancement of nargenicin A1 Dhakal et al 2015). With herboxidiene, the introduction of an expression cassette containing the ACC complex from S. coelicolor A3 (2) in a pSET152 vector (Bierman et al 1992) reduced the herboxidiene yield.…”
Section: Illustration Of Biosynthetic Mechanism Of Herboxidiene In Comentioning
confidence: 99%
“…The heterologous expression of the metK1-sp gene from S. peucetius enhanced the production of pikromycin from S. venezuelae (Maharjan et al 2008) and that of Nargenicin A1 from Nocardia sp. CS682 Dhakal et al 2015). In herboxidiene, the polyketide is decorated with a methyl ester at 25-OH (Fig.…”
Section: Illustration Of Biosynthetic Mechanism Of Herboxidiene In Comentioning
confidence: 99%
“…While NPs exhibit a wide range of pharmacophores and a high degree of stereochemistry (Harvey et al, 2015), novel NPs with better activities still need to be developed. Versatile biological knowledge based synthetic-biology approaches, system-biology guided metabolic engineering techniques, enzymatic modifications, and synthetic chemistry methods can be utilized to maximize the benefit of NPs from the source organism (Dhakal et al, 2015, 2016). Thus, the optimum application of NPs can only be improved with considerable effort based on precise screening, higher production, and desirable structural diversification (Dhakal and Sohng, 2015).…”
mentioning
confidence: 99%